KADAR CD4 SEBAGAI FAKTOR RISIKO GANGGUAN KOGNITIF PADA PENDERITA HUMAN IMMUNODEFICIENCY VIRUS PRAANTIRETROVIRAL - Ni Putu Sukarini,* Anak Agung Raka Sudewi,*Anak Agung Ayu Putri Laksmidewi* (NEURONA, 2017)
INTRODUCTION HUMAN IMMUNODEFICIENCY VIRUS HIV PATIENTS HAVE BEEN ASSOCIATED WITH THE INCIDENCE OF COGNITIVE IMPAIRMENT LOW LYMPHOCYTE T CD4 HAS ALSO ASSOCIATED WITH THE DEVELOPMENT AND PROGRESSION OF HIV COMPLICATIONS